Virtual Learning in the Management of Frail Older Adults in Home Care in home care - Saimovici, Javier Matías; Grande Ratti, María F.; Scozzafava, Silvana M.; Perman, Gastón; Alvarez, Cinthya D.; Magallán, Laura E.; Gallo Acosta, Cristian M.; Cunha Ferré, María F.; Colombo, Valeria P.; Senillosa, Mónica B. (Revista del Hospital Italiano de Buenos Aires, 2026)
Introduction: the rise of home health care (HHC), driven by system advantages, an aging population, and patient preferences, demands specialized training. A university postgraduate course titled "Introduction to the Management of the Frail Elderly in HHC" was designed. This study analyzed student performance, demographics, and feedback. Materials and Methods: the course was virtual, asynchronous, self-paced, free of charge, aimed at healthcare professionals and hosted on the Moodle platform. It was structured into four units: Introduction to HHC systems, HHC Admission, Home assessment, and Discharge from HHC. Teaching methods included audiovisual resources, supplemental readings, and self-assessment activities. The course granted 30-hour certificates. The course awarded certificates for 30 hours after the approval of the 4 self-assessment activities included throughout the training. A cross-sectional study was conducted, including students enrolled between January and August 2025. Data were gathered from educational platform analytics and voluntary feedback surveys from those who completed the course. Results: a total of 1,250 students enrolled, and 218 completed and passed the course (17.44%), with a mean final score of 90.76/100. Participants were 73% female and 82% from Argentina, with medicine and nursing as the primary professions. Feedback was received from 120 graduates (55% response rate). Regarding satisfaction, 99.17% felt the materials facilitated learning, 100% found the virtual campus easy to use, and 98.31% stated the course significantly aided their professional development. The highest-rated aspects were the online modality (64.60%), lecture quality (59.29%), and content (49.56%). Suggestions were received to integrate more rehabilitation topics. Conclusion: this experience was highly valued by graduates and contributed significantly to HHC training, promoting educational accessibility. The completion rate, typically lower in self-administered formats, was low due to a lack of engagement or early dropout. Increasing retention in self-managed modalities remains a challenge, potentially requiring enhanced faculty support if resources permit.